Ferroptosis-related prognostic model of mantle cell lymphoma - Gao Qianwen; Wang Xin; Zhang Yue; Wen Jingjing; Wang Fangfang; Lin Zhimei; Feng Yu; Huang Jingcao; Li Qian; Luo Hongmei; Liu Xiang; Zhai Xinyu; et al. (Open Medicine)
Mantle cell lymphoma (MCL) is a B-cell non-Hodgkin’s lymphoma. Ferroptosis, an iron-dependent programmed cell death, is closely related to cancer prognosis. In this study, we established a model of ferroptosis related genes for prognostic evaluation of patients with MCL.